(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Motor vehicle tax compliance is an important factor in increasing Regional Original Income (PAD). However, the level of taxpayer compliance is still influenced by various factors, such as tax literacy, tax sanctions, and perceived ease of digital services. This study aims to analyze the influence of tax literacy, tax sanctions, and perceived ease of digital services (SIGNAL) on motor vehicle tax compliance among students at Medan State University. The study used a quantitative approach with an associative design. The research sample consisted of 100 active students who owned motor vehicles and were selected using a purposive sampling technique. Data were collected through a Google Form-based questionnaire with a Likert scale, then analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS. The results showed that tax literacy and tax sanctions had a positive and significant effect on motor vehicle tax compliance, with tax sanctions being the variable with the largest influence. Conversely, the perceived ease of digital services through the SIGNAL application did not have a significant effect on taxpayer compliance. Simultaneously, the three variables were able to explain 93.5% of the variation in motor vehicle tax compliance. These findings indicate that increasing tax literacy and implementing effective sanctions play a greater role in improving tax compliance than the convenience of digital services alone.